Electric Field Enhancement Effect of Aluminum Grating With Nanosecond Pulsed Laser Irradiation - Wang, Jiamin; Zhang, Kuo; Yu, Jinghua; Zhang, Yin; Ji, Yanhui; Jirigalantu,; Zhang, Wei; Li, Wenhao; Zheng, Changbin; Chen, Fei (Frontiers in Physics, 2022)
Aluminum grating has wide applications in laser systems and photoelectric equipment. Research on the laser damage characteristics of aluminum grating has guiding significance and application value for improving the laser damage resistance. The aim of this study is to investigate the characteristics of damage induced by nanosecond pulsed lasers on the aluminum grating. To better understand the laser damage characteristics of aluminum grating, herein, Maxwell’s equations were numerically solved according to the finite difference time-domain method, and the electric field model of 1,064 nm Gaussian laser damage aluminum grating was established. The simulation results showed that the light field is modulated by the grating; furthermore, the maximum value of the electric field occurred at the ridge of the grating when the laser is irradiated vertically. Analysis suggested that the electric field distribution is in accordance with the laser energy distribution, and the distribution region of the maximum electric field is a vulnerable location. To further verify the local electric field enhancement effect, based on the 1-on-1 laser damage measurement method, an experimental study of the nanosecond laser (@1,064 nm, 6.5 ns) damage to the aluminum grating was carried out. Moreover, the damage morphology was analyzed using a scanning electron microscope (SEM), and the simulation results showed good agreement with the experimental results.